The statistical parameters analysis of bed load grains in Sungai Kakap Waters, Kubu Raya Regency - Salawati, Salawati; Putra, Yoga Satria; Muhardi, Muhardi; Nurhasanah, Nurhasanah; Adriat, Riza (Acta Aquatica: Aquatic Sciences Journal, 2022)
This study aims to analyze the statistical parameters of bed load grains in Sungai Kakap Waters, Kubu Raya Regency, West Kalimantan Province. Bed load sampling was carried out at seven stations, with five sampling points each. The hydrometer test on the sample was carried out to determine the grain type and size of the bed load, and statistical parameter analysis to determine the mean size, sorting, skewness, and kurtosis. The results showed that the fraction of bed load in the form of sand was 38.54%, silt was 42.11%, and clay was 19.28%. The bed load was dominated by three types namely clay loam, loam, and silt loam. Based on the grain size parameters of the bed load, the mean size (in Ï† units) is 0.94 - 2.24, with the classification of coarse sand to fine sand. The results also showed that the sorting obtained is poorly sorted, the skewness of the sediment is very fine skewed, and the kurtosis is platykurtic.Keywords: bed load; sorting; skewness; kurtosis